The Effect Of Organizational Capital And Institutional Ownership On Tax Avoidance In Indonesian Mining Companies - Desi Andriani Putri; Norman Duma Sitinjak (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to examine the influence of organizational capital and institutional ownership on tax avoidance in mining companies. Tax avoidance is one of the causes of Indonesia's low tax ratio, including in the ASEAN region. Mining companies are an industrial sector that is also relevant to tax avoidance activities because they generally involve large investments. The research method used is quantitative with SPSS analysis tools. The study period is from 2022 to 2024, and the sample was selected using purposive sampling. The number of observations is 36. The results show that organizational capital and institutional ownership influence tax avoidance, with the dominant variable being institutional ownership. An interesting phenomenon observed is: institutional ownership behaves unusually, supporting tax avoidance activities. This behavior is indicated to be caused by policies aimed at clean energy. The use of coal in the future will be limited. Most mining companies in Indonesia are coal mines